Brazilian Life Scripts: Reminiscence Bump Location and Characteristics of Life Events - Felinto,Tuíla Maciel (2022)
Abstract The life script construct refers to the semantic knowledge shared by individuals from a given culture and reflects the expectations about when specific events are supposed to happen. This study aimed to identify whether a life script for Brazilian culture and its characteristics exists. Three hundred and eighty-four participants reported the seven most important events in the life of a hypothetical newborn of their same gender and culture. For each event, they informed an estimate of age and levels of importance, prevalence, and valence. Our results showed that most of the events cited were considered positive and expected to happen before age 30. The ages from 15 to 30 had the most positive events (51.9%). Events before age 15 were rated as more prevalent and important. The results are discussed as representations of lifetime development benchmarks within the Brazilian population and compared to other countries’ data on life scripts.